2017
DOI: 10.1088/1361-6463/aa9604
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of trichel pulse of negative corona discharge in N2–O2mixture

Abstract: Trichel pulse of negative corona discharge in atmospheric air is investigated numerically using a 2D fluid model. The model consists of a hyperbolic cathode tip and a plane anode, and considers 11 kinds of particles and the most important interactions among them. The spatio-temporal evolution of charged species and the electric field are evaluated during the pulse process. During the pulse rising edge, the positive ions accumulate ahead of the tip forming the temporal cathode sheath, significantly enhancing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Since the recombination coefficient, diffusion coefficient and ion mobility are set as constants in the model, then the decay of the pulse should be mainly determined by the electric field, which relates to the space charges. As seen in figure 12, the rising time increases with the radius of cathode curvature, which is in agreement with the previous results [11,17,18,24,32]. However, the pulse rising time remains nearly unchanged with the discharge current increasing.…”
Section: Self-pulsing In a Parallel-plate Configurationsupporting
confidence: 91%
See 2 more Smart Citations
“…Since the recombination coefficient, diffusion coefficient and ion mobility are set as constants in the model, then the decay of the pulse should be mainly determined by the electric field, which relates to the space charges. As seen in figure 12, the rising time increases with the radius of cathode curvature, which is in agreement with the previous results [11,17,18,24,32]. However, the pulse rising time remains nearly unchanged with the discharge current increasing.…”
Section: Self-pulsing In a Parallel-plate Configurationsupporting
confidence: 91%
“…They found that adding oxygen to the above gases increased the voltage range at which Trichel pulses appear. The team further performed numerical simulations of this phenomenon and found that Trichel pulses could be reproduced when the production rate of negative ions was set to 100%, 1% and 0 [18]. Negative ions indeed affect the pulse amplitude and pulse decay edge, but are not necessary for pulse formation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…3. Many twodimensional (2D) fluid models that were built to simulate the whole process of Trichel pulse successfully [31][32][33][34][35][36][37][38] only considered ISEE as the feedback mechanism. The flux of ISEE (Γ e ) is easy to calculate in the fluid models and determined by…”
Section: Ion-induced Secondary Electron Emissionmentioning
confidence: 99%
“…On the other hand, quenching and regenerating of regular pulses are dominated by negative ions in electronegative gases, which is generally well accepted. [30][31][32][33][34][35][36][37][38] However, the pulsed mode has been reported in non-electronegative gases [40][41][42][43][44][45] which challenges the role of negative ions. In this review, we summarize the pulsed mode in non-electronegative gases (whether this mode can be called as Trichel pulse is still not conclusive) since we can get a comprehensive understanding of quenching mechanism through the comparison.…”
Section: Introductionmentioning
confidence: 99%